Impact of Terrorism on Economic Growth in South Asian Country - Saleem, Qasim; Sidra, Sidra; Rauf, Abdur; Siddique, Hafiz Muhammad Abubakar (International Journal of Economics and Financial Issues, 2020)
The association among terrorism and economic growth is crucial from macroeconomics perspective. This analysis is carried out to extract the influence of terrorism on economic growth in Pakistan, incorporating trade, foreign aid and capital for the period of 1981 to 2016. This study applied ARDL bounds testing to inquire the problem and found a co-integration nexus among the used macroeconomic indicators. The evidence shows that terrorism has an inverse relationship with economic growth that is statistically significant. Terrorism may cause to create insecurity and devastating recreational places. There is need to resolve the issue of terrorism to enhance the ability of other economic indicators which cause to enhance the growth of Pakistan. Keywords: Terrorism, Trade, Foreign Aid, ARDL JEL Classifications: F14, F43 DOI: https://doi.org/10.32479/ijefi.9699